HUBUNGAN POLA MAKAN DENGAN STATUS NUTRISI PADA BALITA DI WILAYAH PUSKESMAS JATI KUDUS - Aditya, Muhamad; Faridah, Umi; Wibowo, Edi (Jurnal EDUNursing, 2024)
Nutritional status refers to the condition of the body influenced by dietary patterns and nutrient utilization. This study aims to investigate the relationship between dietary patterns and nutritional status in the working area of Jati Kudus Community Health Center. This research used a quantitative approach with a cross-sectional design involving 63 respondents selected through purposive sampling. Data were collected using a food frequency questionnaire to measure dietary patterns and anthropometric measurements (weight and height) to assess nutritional status. Data analysis employed bivariate analysis using Spearman's Rho test, with a significance level of p < 0.05. The results showed that among 6 respondents with regular dietary patterns, 4 had good nutritional status, 1 had inadequate nutrition, and 1 had excessive nutrition. In contrast, among 57 respondents with irregular dietary patterns, 52 had good nutritional status, 3 had inadequate nutrition, and 2 had excessive nutrition. Statistical analysis revealed a significant relationship between dietary patterns and nutritional status (p = 0.001). The contingency coefficient value was -0.490, indicating a significant negative correlation between dietary patterns and nutritional status in the working area of Jati Kudus Community Health Center.